Sex differences in toxicity and outcomes in patients with sarcoma treated in the perioperative setting at a comprehensive cancer center - Tortorelli, Ilaria; Chiusole, Benedetta; Murtas, Fabio; Galiano, Antonella; Bolshinsky, Maital; Ahcene-Djaballah, Selma; De Toni, Chiara; Vizzaccaro, Salvatore; Maruzzo, Marco; Basso, Umberto; Banzato, Alberto; Coppola, Marina; et al. (Frontiers in Oncology, 2025)
BackgroundThere is an unmet need of personalized strategies taking into account the influence of sex on treatment. Toxicities commonly lead to dose reductions or delays, which may impact outcomes. The current retrospective study investigated the impact of sex on chemotherapy efficacy and toxicity, and evaluated the effect of Relative Dose Intensity (RDI) on survival in patients with sarcoma.Material and methodsData of patients with localized high-grade sarcoma treated at the Veneto Institute of Oncology – IRCCS between 2010 and 2022 were analyzed. Dose reduction or delay were expressed as RDI. Sex differences in RDI, severe adverse events (AEs) and the impact of RDI on disease-free survival and overall survival were analyzed.ResultsA total of 215 patients (women, 46.5%; men, 53.5%) were eligible. Of these, 127 patients were affected by high-grade soft-tissue sarcoma and treated with anthracycline-based chemotherapy. Males were more likely to receive RDI ≥85%, with a lower risk of AEs compared to females. An RDI ≥85 was associated with improved survival outcomes.ConclusionsTo the authors’ knowledge, this is the first study investigating the impact of sex on toxicity and efficacy of perioperative chemotherapy in patients with sarcomas. The increased toxicity in women suggests there is a sex difference in treatment delivery and outcome. Despite a lower RDI, survival outcomes for women were not worse than men. Future studies should aim to better optimize drug dosing according to the sex, with the ultimate goal of increasing therapeutic benefit while limiting toxicity.